2013
DOI: 10.1039/c3bm00197k
|View full text |Cite
|
Sign up to set email alerts
|

The surface charge of anti-bacterial coatings alters motility and biofilm architecture

Abstract: The surface charge of anti-bacterial coatings alters motility and biofi lm architecture This paper represents a systematic study of biofi lm formation onto a range of polymer brush surfaces with the model organism Pseudomonas aeruginosa. The infl uence of physicochemical properties of both the bacterial cell surface and the substrate surface is investigated. The image above shows the start of biofi lm formation onto a polycationic polymer brush surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
173
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 48 publications
16
173
0
1
Order By: Relevance
“…This was mainly by reducing the depressions on the material surfaces by the crystallized deposition of rapamycin on the stent. The obtained results were found supportive when compared to the results of Olena Rzhepishevska et al 27 . The researchers found that the surface charge of antibacterial coatings was more efficient in reducing bacterial adhesion and biofilm formation.…”
Section: Discussionsupporting
confidence: 74%
“…This was mainly by reducing the depressions on the material surfaces by the crystallized deposition of rapamycin on the stent. The obtained results were found supportive when compared to the results of Olena Rzhepishevska et al 27 . The researchers found that the surface charge of antibacterial coatings was more efficient in reducing bacterial adhesion and biofilm formation.…”
Section: Discussionsupporting
confidence: 74%
“…The ability of bacteria to adhere to natural and artificial materials is a first step in biofilm formation, is central for bacterial survival, and has great clinical and environmental relevance [1][2][3]. Initial adhesion is dependent on a large number of parameters [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The FC270 system is particularly useful for the analysis of resulting biofilms using confocal laser scanning microscopy (CLSM). In addition, the FC270 system has the advantage to study biofilm formation in different materials and surfaces [51]. However, there are three major limitations, as they are, a limited visualization the biofilm formation during development, only two biofilms can be J Microbial Biochem Technol ISSN:1948-5948 JMBT, an open access journal Bacteria: Biochemical Physiology inability to collect effluent for analysis of metabolic products generated during biofilm growth [57][58][59].…”
Section: Fc270 Flow-cell Systemmentioning
confidence: 99%
“…Using these devices is possible to detect different analytes between microbes within biofilm. The major advantages of biosensing system are its specificity, sensitivity, experimental reproducibility, as well as ability to analyte detection in optically opaque solutions, also the application both for the study of static and flow biofilms [51][52][53].…”
Section: Biofilm Biosensormentioning
confidence: 99%